Cover Picture: Revisiting the Solution Structure of Ceric Ammonium Nitrate (Angew. Chem. Int. Ed. 26/2015). Issue 26 (12th May 2015) - Demars, Thomas J.; Bera, Mrinal K.; Seifert, Soenke; Antonio, Mark R.; Ellis, Ross J.
<x xml:space="preserve">Abstract</x> A half‐century‐old assertion about the structure of ceric ammonium nitrate (CAN) in solution is challenged. In their Communication on page 7534 ff., R. J. Ellis and co‐workers show that in HNO3, CAN is a dinuclear CeOCe complex. The bridging oxygen (the guy with the hat) would usually be attacked and devoured by the HNO3 sharks. However, he is protected by the Ce "life rings" on either side, and so he is safe. The structure suggests that CAN can act as a two‐electron‐transfer reagent and not, as generally assumed, a one‐electron‐transfer reagent.